(3dbW GdefGaY aj Yde GdWHs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI(B: (3GdMeO ddg GdMcje aj JOHjQg GdYdje ai JbOjQg deG QCjJ Yde GdWH YdekG UMjMkG bO fHg Ydjg GdbQBf GdYRjR hGdfbd GdUMjM hTgO HUMJg GdYbd s
(3BNQgG (B:s
(3EPG eQV GdEfSGf GdeUMM GdPi dGjcGO jeQV cGf eQVg eNhakG , hGddg YR hLd CYde hCMce s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG JbWjYs
(3GdfSNI ebGHdIs
(3fgGjI GdfSN ddeNWhW cGf SfI (B826 (3g`s
(3HChdgG agQS ddehVhYGJ s
(3hgj oebGHdI hoeUMMI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs